2020
DOI: 10.1155/2020/2376581
|View full text |Cite
|
Sign up to set email alerts
|

Gyejigachulbutang (Gui‐Zhi‐Jia‐Shu‐Fu‐Tang, Keishikajutsubuto, TJ‐18) in Degenerative Knee Osteoarthritis Patients: Lessons and Responders from a Multicenter Randomized Placebo‐Controlled Double‐Blind Clinical Trial

Abstract: Background. Gyejigachulbutang (GUI-ZHI-JIA-SHU-FU-TANG, GCB) is an herbal formula widely prescribed in traditional East Asian medicine practice for arthritis and muscle pain. We evaluated the efficacy and safety of GCB for degenerative knee osteoarthritis (KOA). Methods. Eighty patients with KOA were randomly assigned to the GCB group or the placebo group in a 1 : 1 ratio in two Korean medicine hospitals. Patients took GCB or placebo three times a day for 4 weeks. Primary outcome was the change in the visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Increasing evidence has demonstrated that complementary and alternative medicine is important and effective in the management of different chronic diseases, including urinary retention [ 3 ], degenerative knee osteoarthritis [ 4 ], gastroesophageal reflux disease [ 5 ], chronic idiopathic urticaria [ 6 ], and shigellosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that complementary and alternative medicine is important and effective in the management of different chronic diseases, including urinary retention [ 3 ], degenerative knee osteoarthritis [ 4 ], gastroesophageal reflux disease [ 5 ], chronic idiopathic urticaria [ 6 ], and shigellosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%